Primary hyperparathyroidism versus familial hypocalciuric hypercalcemia: a challenging diagnostic evaluation in an adolescent female - Mustafa Tosur; Monica E. Lopez; David L. Paul (Korean Society of Pediatric Endocrinology, 2019)
Primary hyperparathyroidism (PHPT) and familial hypocalciuric hypercalcemia (FHH) have significantly different treatment approaches, so physicians must be careful to differentiate these 2 diseases. Herein, we report a 14-year-old female who presented with symptomatic hypercalcemia (12 mg/dL; reference range, 9.2-10.7 mg/dL), elevated intact parathyroid hormone (iPTH) (236 pg/mL; reference range, 9-69 pg/mL), and vitamin D deficiency (6 ng/mL; reference range, ≥ 20 ng/mL). On numerous occasions, her 24-hour urine calcium was more than 4 mg/kg/day, consistent with PHPT, but her fractional excretion of calcium on 24-hour urine collection was consistently below 1%, in line with FHH. 99mTc-Sestamibi scan failed to detect any abnormalities. However, a 4-dimensional computed tomography scan of the neck revealed a right superior parathyroid adenoma which was excised with a focused parathyroidectomy. Although the patient's calcium and iPTH levels normalized, her nonspecific symptoms persisted. This case illustrates both the challenges of differentiating PHPT from FHH and the limitations of a first-line imaging tool in identifying a parathyroid adenoma.